X-box Binding Protein 1 is a Potential Immunotherapy Target in Ovarian Cancer - Jiang, Yanhui; Yang, Lewei; Jiang, Ling; Yu, Wenyan; Jin, Zhongwen; Qiu, Yeqing; Liao, Yifeng; Liu, Jihong; Zhang, Hongyu (Frontiers in Genetics, 2022)
The allure of potentially dramatic and durable responses to immunotherapy has driven the study of several immune checkpoint inhibitor (ICI) agents in ovarian cancer. However, the results of immune ICI therapy in ovarian cancer have been rather disappointing. It is important to understand the reasons for the poor efficacy of ICI in ovarian cancer and to look for new targets for immunotherapy. To solve this problem, ovarian cancer–associated datasets were individually collected from Gene Expression Profiling Interactive Analysis 2 (GEPIA2), cBioPortal, Kaplan-Meier Plotter and Tumor and Immune System Interaction Database (TISIDB), and subsequently performed to expression, prognostic, pathological correlation, genomic and immunologic analyses of all well-identified immune checkpoints. We concluded that those reported immune checkpoints might not be ideal targets for ovarian cancer immunotherapy. Intriguingly, the genomic alteration of X-box binding protein 1 (XBP1), the important mediator of chemotherapy-induced cancer immunogenic cell death, was found to be a potential coregulator of immune checkpoints in ovarian cancer. Importantly, XBP1 was detected to be highly expressed in ovarian cancer, and high XBP1 expression significantly favors both overall survival（OS）and disease-free survival (DFS) of patients with ovarian cancer. More importantly, XBP1 was further observed to be closely related to anti-tumor immunity in ovarian cancer, including multiple T-cell signatures and immune effector cells. In all, upregulating XBP1 rather than targeting immune checkpoints represents a potentially more efficient approach for ovarian cancer therapy.